Income inequality and saving in a class society: The role of ordinal status - Rein Haagsma (Kiel Institute for the World Economy (IfW), 2018)
This paper examines the impact of income growth and income inequality on household saving rates and payoffs in a non-cooperative game where each player's payoff depends on her present and future consumption and her rank in the present-consumption distribution. The setting is a pooling equilibrium with three clusters of successive income groups, each cluster having its own present-consumption standard and rank in the present-consumption distribution. In this way the analysis addresses the saving behaviour and welfare of three social classes: the lower, middle and upper class. The author finds explanations for the Easterlin paradox and the Kuznets consumption puzzle and concludes that rank concerns tend to weaken the standard effect of inequality on aggregate saving.
Keywords: C72; D31; D62; E21; I31; Z10; 330; status; relative consumption; saving; income inequality; income growth